Formation of metastable phases by spinodal decomposition - Ricard Alert; Pietro Tierno; Jaume Casademunt (Nature Communications, 2016)
Metastable phases are usually formed through nucleation, upon overcoming an energy barrier. Here, Alert et al. theoretically predict and experimentally verify the unexpected formation of a metastable phase by spinodal decomposition through direct phase separation from an unstable phase.